2008
DOI: 10.1002/jcu.20509
|View full text |Cite
|
Sign up to set email alerts
|

Improved prenatal aneuploidy screening using the novel advanced first‐trimester screening algorithm: A multicenter study of 10,017 pregnancies

Abstract: : AFS can markedly reduce the rate of false positive test results. If these results are confirmed by larger multicenter studies, the new AFS will represent a great improvement in fetal aneuploidy screening. (c) 2008 Wiley Periodicals, Inc. J Clin Ultrasound, 2008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
12
1
1
Order By: Relevance
“…However, they are in contrast to the studies of Schmidt et al [4,12] . They argued that by using fetal NT and maternal serum biochemistry without the maternal age-related risk, the false-positive rate can be reduced by 22%.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, they are in contrast to the studies of Schmidt et al [4,12] . They argued that by using fetal NT and maternal serum biochemistry without the maternal age-related risk, the false-positive rate can be reduced by 22%.…”
Section: Discussioncontrasting
confidence: 54%
“…Our study population is representative for a screening population as general obstetricians and gynecologists have performed the examination. In the study population of Schmidt et al [4] , the overall prevalence of trisomy 21 was 1 in 181 despite the average maternal age of 31.3 years. This overrepresentation of chromosomally abnormal fetuses is most probably due to inclusion of data from referral centers such as a university center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to the established approach to first trimester screening, this innovative model does not take maternal age into account, as previous studies have shown that this would increase the number of falsenegative cases in younger mothers and the number of false-positive cases in older mothers without significantly improving the detection rate [5,6]. However, the most important innovation is the direct assessment of the risk of fetal aneuploidy through the assessment of the three-dimensional spatial arrangement of plotted data from screening data instead of the sequential multiplication of estimated risk from each of the measurements taken.…”
Section: Importance Of This Modelmentioning
confidence: 99%
“…Individual risk assessments for aneuploidies are obtained from the comprehensive interpretation of the fetal nuchal translucency thickness in mm according to the crown-rump-length (NT), which is measured by ultrasound, and the maternal blood serum concentration of pregnancy associated plasma protein A (PAPP-A), and free β-human chorionic gonadotropin (fβ-hCG) [3]. Different methods have been developed for risk calculation [3][4][5][6][7]. Recent studies suggested the potential of a novel computer model called "Advanced First Trimester Screening three dimensional (AFS-3D)" [8][9][10] in which each parameter is assigned to one axis in a three dimensional coordinate system (Figure 1).…”
Section: Introductionmentioning
confidence: 99%